2017
DOI: 10.1177/1479972316687209
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use of dry powder inhalers versus pressurized metered-dose inhalers devices in adult patients with chronic obstructive pulmonary disease or asthma: An observational comparative study

Abstract: Numerous patients with chronic obstructive pulmonary disease (COPD) and asthma do not use inhaler devices properly, which can contribute to poor disease control. The objective of this study is to assess the technical and safety use of dry powder inhalers (DPIs) versus pressurized metered-dose inhalers (MDIs) in adult patients with COPD or asthma in Lebanon. A concurrent, prospective comparative observational study was conducted at one hospital and 15 community pharmacies in Lebanon. Over a period of 18 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Aerosol inhalation is considered the primary route of administering medication to manage asthma [1,4] and other obstructive airway diseases [6,7]. However, correct inhaler use is often suboptimal in patients with obstructive airway disease, resulting in reduced therapeutic benefit [6,12]. In particular, patients who are older, have underlying pulmonary symptoms, and/or who have received less education and training regarding correct use of their specific device can experience difficulty with achieving correct inhalation technique [12,14,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerosol inhalation is considered the primary route of administering medication to manage asthma [1,4] and other obstructive airway diseases [6,7]. However, correct inhaler use is often suboptimal in patients with obstructive airway disease, resulting in reduced therapeutic benefit [6,12]. In particular, patients who are older, have underlying pulmonary symptoms, and/or who have received less education and training regarding correct use of their specific device can experience difficulty with achieving correct inhalation technique [12,14,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, correct inhaler use is often suboptimal in patients with obstructive airway disease, resulting in reduced therapeutic benefit [6,12]. In particular, patients who are older, have underlying pulmonary symptoms, and/or who have received less education and training regarding correct use of their specific device can experience difficulty with achieving correct inhalation technique [12,14,31,32]. Good inhaler competence appears to be a contributor to the beneficial outcomes and rates of patient satisfaction achieved with the B/F Easyhaler in the present study of older patients with asthma or COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also use of DPIs does not require careful coordination as in case pMDIs. 16 Another reason for higher satisfaction in DPI users could be less strong taste and hence more liking for the taste of DPI, more amount of drug that is felt reaching the throat, slight moist feeling in throat after inhalation (no dryness) and few adverse effects with the device.…”
Section: Discussionmentioning
confidence: 99%
“…15 An observational study by Ramadan et al found that higher percentage of DPI users found their device easy to use as compared to pMDIs. 16 Aggarwal et al, conducted a comparative study using pMDIs and DPIs and observed that patients were more satisfied with the use of metered dose inhalers and hence showed better adherence than patients on DPIs. 17 India, particularly Haryana, has poor literacy rate so educating the patients for the proper use of such devices is a real challenge.…”
mentioning
confidence: 99%